Key sociodemographic factors and food packaging attributes associated with poor diet quality among rural Americans: a cross-sectional survey study - David C Lee; Christian A Koziatek; Lorna E Thorpe; Leonardo Trasande; Haley L Motola; Karen S Holden; Jill Hubert-Simon; Nathan Wise; Anirudh Prabu; Kelly M Doran (BMJ Open)
Objectives Rural residents face unique challenges that contribute to poor diet quality and health. The objective of this study was to assess diet quality using the Alternative Healthy Eating Index (aHEI) among residents of a rural New York county with poor health outcomes, and identify geographic and individual-level factors associated with lower diet quality.Design We performed a cross-sectional study using survey data and multivariable linear regression analyses, supplemented by geographic distribution assessment of aHEI scores.Setting Sullivan County, New York, a rural county with poor health outcomes.Participants Households in Sullivan County who responded to a dietary and sociodemographic health survey in 2021–2022.Outcome measures The primary outcome was the aHEI score and its dietary subscores. Secondary measures included sociodemographic characteristics, receipt of income assistance, financial hardship, food and housing insecurity, primary food store type, distance to food store and frequency of canned or plastic-wrapped food consumption.Results The overall survey response rate was 42.5%. The mean aHEI score was 56.5 (SD: 11.9), normally distributed across respondents. Lower aHEI scores were associated with not completing high school (10.0 points lower vs college graduates, p<0.01), reporting a disability (3.5 points lower, p<0.01), experiencing food insecurity (3.0 points lower, p<0.01) and frequent consumption of canned foods (6.2 points lower compared with those who never consumed canned foods, p<0.01). Geographic analysis revealed clustering of predictors but no substantial geographic clustering of aHEI scores.Conclusions Poor diet quality in rural areas is associated with education level, disability, food insecurity and canned food consumption. These findings highlight potentially modifiable risk factors and support the need for targeted interventions to improve diet quality and reduce health disparities in rural populations.